Strangers and Foreigners: Trust and Attitudes toward Citizenship - Graziella Bertocchi; Arcangelo Dimico; Gian Luca Tedeschi (Institute of Labor Economics (IZA), 2022)
We analyze the relationship between natives' attitudes towards citizenship acquisition for foreigners and trust. Our hypothesis is that, in sub-Saharan Africa, the slave trade represents the deep factor behind contemporary attitudes toward citizenship, with more intense exposure to historical slave exports for an individual's ethnic group being associated with contemporary distrust for strangers, and in turn opposition to citizenship laws that favor the inclusion of foreigners. We find that individuals who are more trusting do show more positive attitudes towards the acquisition of citizenship at birth for children of foreigners, that these attitudes are also negatively related to the intensity of the slave trade, and that the underlying link between trust and the slave trade is confirmed. Alternative factors—conflict, kinship, and witchcraft beliefs—that, through trust, may affect attitudes toward citizenship, are not generating the same distinctive pattern of linkages emerging from the slave trade.
Keywords: J15; K37; N57; O15; Z13; 330; citizenship; trust; slave trade; migration; ethnicity; conflict; kinship; witchcraft